Wireless Network Security Analysis Using the Penetration Testing Method in a Campus Environment - Abil Alwi Prayoga; Siti Khodijah (Journal of Computer Science, Artificial Intelligence and Communications, 2026)
The rapid development of information technology has increased the utilization of wireless networks in higher education environments to support academic activities, administrative services, and digital communication. However, the widespread use of wireless networks also introduces various cybersecurity risks due to the open nature of wireless communication media. This study aims to analyze the security level of campus wireless networks using the penetration testing method to identify vulnerabilities and evaluate existing security mechanisms. The research applies a systematic penetration testing approach consisting of several stages, including information gathering, scanning, vulnerability assessment, exploitation testing, and reporting. The testing process focuses on analyzing wireless configurations, authentication mechanisms, encryption implementation, and potential unauthorized access risks. The results indicate that although the campus wireless network has implemented security protocols such as WPA/WPA2 and encryption mechanisms, several vulnerabilities remain, particularly related to weak password policies, limited access control, and insufficient network monitoring. Based on the vulnerability assessment, improvements are recommended through the implementation of stronger authentication methods, enhanced password management policies, continuous network monitoring, and periodic security evaluations. This research demonstrates that penetration testing is an effective method for identifying security weaknesses and improving wireless network protection. The findings are expected to provide valuable insights for educational institutions in developing more secure, reliable, and sustainable wireless network infrastructures.